THE INFLUENCE OF COMPETENCY AND WORKLOAD ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS DURING THE COVID-19 PANDEMIC - Argyanti, Daffa; Sari, Bunga Tri Indah; Eprilyastuti, Faurizka; F, Neng Dea Nadri; Vesta, Jordy Sanrin; Hayati, Neuneung Ratna (CENTRAL ASIA AND THE CAUCASUS, 2022)
The Covid-19 Pandemic has impacted various activities, including implementing elementary schools' teaching and learning processes. This study aims to examine the model of the relationship between workload and competence on performance perceived by elementary school teachers when they carry out the teaching and learning process from home. This research uses a survey involving 133 elementary school teachers in the city of Bandung. The data analysis was carried out at the individual level and hypothesis testing using Multiple Linear Regression analysis. Empirical test results show that the competence of elementary school teachers has a positive influence on performance during the Covid-19 Pandemic. However, empirically, the hypothesis that workload hinders performance is not supported. This research has limitations related to the generalization of the results due to respondents who only teach in the city of Bandung. In addition, this research does not differentiate between teachers at each level and uses a cross-sectional design, including the risk of common method bias. This paper is expected to explain that teachers in elementary schools are critical success factors for students when learning is carried out from home due to Covid-19. However, the performance produced by elementary school teachers can be influenced by their competencies. Upskilling and adaptation to the emergence of additional workloads must be made quickly. Therefore, this study provides insight that it is necessary to accelerate competence and adjust the workload of elementary school teachers so that the quality of the resulting learning does not experience a decrease in quality.